Ablation of typical atrial flutter using a novel non-fluoroscopic electromagnetic catheter tracking system. (April 2014) - Kircher, Simon; Rolf, Sascha; Hindricks, Gerhard; Sommer, Philipp
Typical atrial flutter is characterized by a stable macro-reentrant circuit around the tricuspid annulus with the cavotricuspid isthmus serving as the critical zone of slow conduction. Catheter ablation targeting this isthmus provides a curative and safe treatment option for the vast majority of patients with atrial flutter. The conventional ablation approach using fluoroscopy for catheter visualization and navigation, however, is associated with substantial radiation exposure to both patients and healthcare personnel. Recently, a novel non-fluoroscopic electromagnetic catheter tracking system has been introduced that enables integration of 3D catheter navigation into the environment of prerecorded conventional 2D fluoroscopy. The feasibility, safety and efficacy of this system have been demonstrated in a variety of invasive electrophysiological procedures. In nonrandomized clinical trials, utilizing the nonfluoroscopic catheter tracking system to support catheter ablation for atrial flutter was associated with a substantial reduction in fluoroscopy time and radiation exposure at similar rates of acute procedural success.